Criminological analysis of crimes against property - Головкин, Б. М. (Theory and practice of jurisprudence, 2016)
Analyzed the level, structure and dynamics of the more common non-violent self-serving and selfish violent crimes against property, as well as to study the main features of the individual offender and especially his criminal behavior